Polymer Spraying for Aerosol Jet Etching of Dielectrics for 156-mm Silicon Wafers. Issue 1630 (22nd January 2014) - Rodriguez, John; Wang, Xi; Subbiah, Jegadesan; Jie, Cui; Lennon, Alison J.
ABSTRACT: The front surface of dielectric passivated silicon wafers were spray coated with polyacrylic acid (PAA) using an ultrasonic coating system. A simple model was proposed to correlate the degree of coverage with the number of spray passes. The sprayed PAA films enabled good etching of the dielectric, using a process referred to as aerosol jet etching (AJE), despite the fact that the PAA thickness was non-uniform over the substrate. The AJE tip-to-substrate distance and diameter of the tip were tuned to balance process throughput and the etched line width. Controlling the level of condensation in the aerosol jet printer (AJP) fluid path was critical for etching 156-mm pseudo square silicon wafers.